2016
DOI: 10.1007/s00441-016-2386-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of myoid and endothelial cells in the peritubular wall during contraction of the seminiferous tubule

Abstract: The wall of the seminiferous tubule in rodents consists of an inner layer of myoid cells covered by an outer layer of endothelial cells. Myoid cells are a type of smooth muscle cell containing α-actin filaments arranged in two independent layers that contract when stimulated by endothelin-1. The irregular surface relief of the tubular wall is often considered a hallmark of contraction induced by a variety of stimuli. We examine morphological changes of the rat seminiferous tubule wall during contraction by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…15c). Our observations of coaxially oriented myofilament bundles in a given LSMC are obviously in contrast to claims of some other authors that-at least in rodents-in the same LSMC region myofilament bundles may exist that are oriented in different directions (see e.g., Losinno et al 2012Losinno et al , 2016. Some AJ-like structures connecting LSMCs appear-at relatively low frequency-as rather short end-on-end junctions.…”
Section: Compositional Heterogeneities Of If Proteins In Lsmcs Of Percontrasting
confidence: 96%
See 1 more Smart Citation
“…15c). Our observations of coaxially oriented myofilament bundles in a given LSMC are obviously in contrast to claims of some other authors that-at least in rodents-in the same LSMC region myofilament bundles may exist that are oriented in different directions (see e.g., Losinno et al 2012Losinno et al , 2016. Some AJ-like structures connecting LSMCs appear-at relatively low frequency-as rather short end-on-end junctions.…”
Section: Compositional Heterogeneities Of If Proteins In Lsmcs Of Percontrasting
confidence: 96%
“…This general classification as LSMCs supports and extends the very early classification based on transmission electron microscopy (Ross and Long 1966;Ross 1967) but is now also based on a series of cell and molecular biological results: these LSMCs are the only SMCs which grow in situ in distinct monolayers of tight-packed monolayers and are very closely and stably connected by some endon-end and many vertical area adhaerens AJ-like structures (see below). Understandably, this latter special cell architectonic organization has not been noted in the numerous scanning electron microscopy preparations as these have only presented the outermost total cell surfaces of entire LSMC monolayers (see e.g., Tung and Fritz 1987;Palombi et al 1992;Tripiciano et al 1996Tripiciano et al , 1997Tripiciano et al , 1999Romano et al 2005;Losinno et al 2016). Clearly, these LSMCs are not just Bmyoid^(meaning only Blooking like muscle^but not being a real muscle) as it had been proposed by Fawcett and co-workers (e.g., Fawcett et al 1969;Fawcett 1994), who described them as Bepithelial in shape and mode of association^with an Batypical shape^for a muscle cell.…”
Section: The Lsmcs Of the Peritubular Walls-a Special Kind Of Smooth mentioning
confidence: 99%
“…Maekawa et al (1996) reported that "the frequency of the pressure change in the seminiferous tubule is 0.17-0.23Hz, and is lower than that of epididymal ducts where several muscle layers and rich innervation are present." The diameter of the rat STs shows a 40% reduction when they contract (Losinno et al, 2016). When the function of the peritubular myoid cell (PMC) is disrupted, the luminal flow in the ST is modulated, resulting in dilation of the ST (Uchida et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The transport of the spermatozoa is induced by the peristaltic motion of the ST to approach the epididymis (Maekawa et al ., 1996). Maekawa et al (1996) reported that “the frequency of the pressure change in the seminiferous tubule is 0.17-0.23Hz, and is lower than that of epididymal ducts where several muscle layers and rich innervation are present.” The diameter of the rat STs shows a 40% reduction when they contract (Losinno et al ., 2016). When the function of the peritubular myoid cell (PMC) is disrupted, the luminal flow in the ST is modulated, resulting in dilation of the ST (Uchida et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%